How prisoners and their partners experience the maintenance of their relationship during a prison sentence. (5th November 2019) - De Claire, Karen; Dixon, Louise; Larkin, Michael
Abstract: Research shows that intimate relationships, and their maintenance via prison visits, have a positive impact on factors associated with prisoner well‐being and reduced likelihood of recidivism. It is therefore in the interest of corrections, government, and wider society to enable prisoners to maintain healthy relationships with their family and intimate partners throughout their prison sentence. Despite this evidence, little is known about how prisoners experience the maintenance of a significant intimate relationship in prison. This study aims to explore heterosexual couples' experiences in maintaining their well‐established intimate relationships, while the male partner is incarcerated. Four main themes were identified: how they experienced "having a special connection" that they were motivated to maintain; "coping with challenges and threats" to that connection; "developing reciprocal behaviours" to meet those challenges; and "maintaining a belief in the future." Implications for how the relational context of rehabilitation can best be supported is considered.